Legal Threats to Home Industry Prostitution Service Providers - Dimas Kurniawan; Amalia Tri Fajarianti; Dewi Novita; Diana Novita; Deni Setiyawan (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
The phenomenon of prostitution is an old phenomenon that has occurred for centuries. The rise of prostitution in Indonesia is growing along with progress ranging from transportation to technological developments. Apart from the development of science, the rapid growth of prostitution is also caused by fulfilling the essence of society's hedonistic lifestyle. Nowadays prostitution can be easily accessed through electronic technology and social media. The problem of prostitution can become a serious social problem if left untreated. One of the impacts of free prostitution is health problems, disease transmission from free sex can spread quickly and to anyone. In Indonesian law, prostitution is an act that is contrary to the rules of criminal law. The provisions are in Article 506 of the Criminal Code which clearly threatens prison sentences and fines. Keywords: Prostitutions, Criminology, Lifestyles.